2010
DOI: 10.1007/s12185-010-0655-0
|View full text |Cite
|
Sign up to set email alerts
|

Blastic plasmacytoid dendritic cell neoplasm should be treated with acute leukemia type induction chemotherapy and allogeneic stem cell transplantation in first remission

Abstract: Blastic plasmacytoid dendritic cell (BPDC) neoplasm is a rare but clinically aggressive tumor known to be derived from the precursors of plasmacytoid dendritic cells (CD123+) with a high frequency of cutaneous and bone marrow involvement. Though majority of the patients initially respond to multi-agent chemotherapy, most would relapse within a year. We hereby report a patient with disseminated cutaneous BPDC with marrow involvement diagnosed by typical histo-pathological and flow-cytometric findings. He was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
0
17
0
2
Order By: Relevance
“…Unfortunately, transplantation beyond CR1 may have an adverse impact on both OS and progression-free survival (PFS) [42][43][44] ; thus, timing and patient selection remain important concerns. In their summary of the literature from 1994 to 2002, Reimer et al 39 reported on 10 patients: 6 patients treated with allo-SCT and 4 patients treated with autologous SCT (auto-SCT).…”
Section: Hematopoietic Sctmentioning
confidence: 99%
“…Unfortunately, transplantation beyond CR1 may have an adverse impact on both OS and progression-free survival (PFS) [42][43][44] ; thus, timing and patient selection remain important concerns. In their summary of the literature from 1994 to 2002, Reimer et al 39 reported on 10 patients: 6 patients treated with allo-SCT and 4 patients treated with autologous SCT (auto-SCT).…”
Section: Hematopoietic Sctmentioning
confidence: 99%
“…Actualmente se considera la mejor opción el TAloCPH durante la primera remisión completa, aumentando la supervivencia global y supervivencia libre de enfermedad, sin recaídas dentro de los primeros 27 meses 18,19 . En nuestros pacientes el tratamiento consistió en HiperCVAD seguido de TAloCPH con una media de seguimiento de 14,6 meses.…”
Section: Discussionunclassified
“…However, BPDCN widely disseminates, and despite an initial response to systemic chemotherapy, relapses are frequent in the absence of allogeneic hematopoietic stem cell transplantation (allo-SCT). Treatment with acute myeloid leukemia (AML)-type induction chemotherapy regimens followed by allo-SCT at the first complete remission has been advocated (4,5). Although the older age of the patient populations presents a challenge to the treating hematologist/oncologist, reduced-intensity conditioning allo-SCT has been shown to be effective in patients up to 70 years of age (6).…”
Section: Discussionmentioning
confidence: 99%